2010
DOI: 10.4103/1319-3767.61238
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of rapid urease test in diagnosing Helicobacter pylori infection in patients using NSAIDs

Abstract: Background/Aim:This study aimed to determine the effect of nonsteroidal anti-inflammatory drugs (NSAIDs) on the results of rapid urease test (RUT).Patients and Methods:The study evaluated 210 consecutive patients for the diagnosis of Helicobacter pylori (H. pylori) infection. They were divided into case and control groups based on history of NSAID use (n=70 each). Two biopsy specimens were collected from antrum and corpus of stomach during endoscopy and sent for rapid urease testing and histopathology. Sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…[32] Like many other studies done till date, we too conclude that RUT is a good initial test as it is rapid, cheap, and easily available as compared to other HP detection tests. [33][34][35] We found that HP infection was more prevalent in T2DM than in nondiabetics (P < 0.00001). Several other studies too found that diabetes patients had higher prevalence of HP infection.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Like many other studies done till date, we too conclude that RUT is a good initial test as it is rapid, cheap, and easily available as compared to other HP detection tests. [33][34][35] We found that HP infection was more prevalent in T2DM than in nondiabetics (P < 0.00001). Several other studies too found that diabetes patients had higher prevalence of HP infection.…”
Section: Discussionmentioning
confidence: 99%
“…12 However reports of Foroutan et al were not on par with the findings which state that only 65% of cases were positive for urease in their study. 13 These differences may be due to the difference in the geographic distribution of the study, variability in the study group population and the sensitivity and specify of the commercial kits used in the study.…”
Section: Resultsmentioning
confidence: 99%
“…This justifies why these patients do not benefit from anti-acid therapy [ 24 ], and in our study, this is proven. Moreover, different studies on various subjects have published the regarding the above results [ 25 ] [ 26 ] [ 27 ] [ 28 ] [ 29 ].…”
Section: Discussionmentioning
confidence: 99%